Foreign labour migration and the economic crisis in the EU: Ongoing and remaining issues of the migrant workforce in Germany - Anna Myunghee Kim (Institute for the Study of Labor (IZA), 2010)
This paper provides an evaluation of the status of migrant workers in Germany amidst the global financial crisis. Findings of the study are drawn from the latest available data on the labour market performance of native-German and non-German migrant workers as well as other socioeconomic integration measures of the receiving state. Compared to the experience of migrants in most of the major receiving states of the EU, the status of the predominantly low-skilled sector-employed migrant workers in Germany, where primarily the skilled-workforce concentrated industries of high-value products is affected, has remained unchanged during the crisis. On the other hand, marginalisation of the ethnic and national minority population appears to be a persistent phenomenon marked by long-standing labour market exclusion. This is manifested in over two decades of double-digit unemployment rates of the foreign migrant population in the former 'guest-worker' importing country. This implies for the economy the need to settle long-term problems and implement strategies towards a better labour market integration of the minority migrant population beyond the recent recession.
urn:nbn:de:101:1-201010133173
Keywords: F22; J61; O15; 330; global financial crisis; low-skilled sector; migrant workers; guest-workers; labour market integration; minority migrant population